The acyl-glucuronide metabolite of ibuprofen has analgesic and anti-inflammatory effects via the TRPA1 channel. (April 2019) - De Logu, Francesco; Li Puma, Simone; Landini, Lorenzo; Tuccinardi, Tiziano; Poli, Giulio; Preti, Delia; De Siena, Gaetano; Patacchini, Riccardo; Tsagareli, Merab G.; Geppetti, Pierangelo; Nassini, Romina
Graphical abstract: Abstract: Ibuprofen is a widely used non-steroidal anti-inflammatory drug (NSAID) that exerts analgesic and anti-inflammatory actions. The transient receptor potential ankyrin 1 (TRPA1) channel, expressed primarily in nociceptors, mediates the action of proalgesic and inflammatory agents. Ibuprofen metabolism yields the reactive compound, ibuprofen-acyl glucuronide, which, like other TRPA1 ligands, covalently interacts with macromolecules. To explore whether ibuprofen-acyl glucuronide contributes to the ibuprofen analgesic and anti-inflammatory actions by targeting TRPA1, we used in vitro tools (TRPA1-expressing human and rodent cells) and in vivo mouse models of inflammatory pain. Ibuprofen-acyl glucuronide, but not ibuprofen, inhibited calcium responses evoked by reactive TRPA1 agonists, including allyl isothiocyanate (AITC), in cells expressing the recombinant and native human channel and in cultured rat primary sensory neurons. Responses by the non-reactive agonist, menthol, in a mutant human TRPA1 lacking key cysteine-lysine residues, were not affected. In addition, molecular modeling studies evaluating the covalent interaction of ibuprofen-acyl glucuronide with TRPA1 suggested the key cysteine residue C621 as a probable alkylation site for the ligand. Local administration of ibuprofen-acyl glucuronide, but not ibuprofen, in the mouse hind paw attenuated nociception by AITC and other TRPA1 agonists and the early nociceptive response (phase I) to formalin. Systemic ibuprofen-acyl glucuronide and ibuprofen, but not indomethacin, reduced phase I of the formalin response. Carrageenan-evoked allodynia in mice was reduced by local ibuprofen-acyl glucuronide, but not by ibuprofen, whereas both drugs attenuated PGE2 levels. Ibuprofen-acyl glucuronide, but not ibuprofen, inhibited the release of IL-8 evoked by AITC from cultured bronchial epithelial cells. The reactive ibuprofen metabolite selectively antagonizes TRPA1, suggesting that this novel action of ibuprofen-acyl glucuronide might contribute to the analgesic and anti-inflammatory activities of the parent drug.